ANALISIS SEKTOR BASIS DAN NON BASIS DI KABUPATEN BOLAANG MONGONDOW TIMUR - Alen Gifthovel Sumayow; Paulus A. Pangemanan; Ellen G. Tangkere (Sam Ratulangi University, 2018)
This study aims to determine what sectors are the base and non-base sectors in East Bolaang Mongondow Regency. This study was conducted for three months starting from August to November 2017 in East Bolaang Mongondow Regency. The data used in this study is secondary data obtained from the Central Bureau of Statistics (BPS) Kotamobagu City. The data is in though using descriptive analysis research method. The research result showed that the sectors that are the base sector in East Bolaang Mongondow Regency are Electricity and Gas Procurement, Construction, Information and Communication, and Other Services sectors.*jnkd*.